The Role of Salivary Gland Scintigraphy in the Evaluation of Salivary Gland Dysfunction in Uncontrolled Type II Diabetic Patients - B. Senthilkumar (World Journal of Nuclear Medicine, 2013)
The aim of the present study was to evaluate the salivary gland dysfunction in patients with uncontrolled type II diabetes using salivary gland scintigraphy and then to compare these ratios with quantitative whole salivary secretion rates. Using a gamma camera (siemens-diacam) equipped with a low energy all-purpose collimator, 32 uncontrolled type II diabetic patients and 30 normal healthy patients were studied by injecting a radio isotope (technetium 99m pertechnetate) about 5 mCi was injected intravenously in to anticubital vein and the activity was measured for the 1 st , 20 th and 40 th min. At 20 min after injection, vitamin C chewable tablet was given to stimulate the secretion and continued until the end of the study period (40 min). Before scintigraphy, salivary sampling was carried out in both diabetic and normal individuals in a quiet room, saliva was allowed to accumulate and was expectorated into the collecting vessel approximately once a minute for 15 min and the volume was recorded as Unstimulated salivary flow rate and after 5 min break vitamin C chewable tablet was given to stimulate the secretion and the patient was asked to expectorate the saliva in the collecting vessel for 5 min. The expectorated volume was recorded as stimulated salivary flow rate. The mean of the measurements of scintigraphic ratio and salivary secretion rates were compared using the paired Student′s t-test. The scintigraphic mean uptake and excretory ratio (ER) and the salivary flow rates were correlated. The result shows that there was a significant correlation between salivary flow rate and scintigraphic uptake and ER. However, statistically significant result could not be derived as it may be due to smaller sample size and marginal difference in the scintigraphic values between the groups. Salivary gland scintigraphy plays a significant role in the evaluation of salivary gland dysfunction. However, its role as an independent investigative procedure in the evaluation of salivary gland dysfunction requires a study with a larger sample size, may yield a statistical significant result and it can also act as an adjunct along with salivary flow rate procedure.